Deconstructing the classroom - Ramos, M. (International Conference - Decolonizing the Academy, Centre of African Studies, University of Edinburgh, 20-22 April 2016, 2016)
The academic teaching model that is globally pursued and reinforced is one that ultimately derives from the European universities’ once intimate relationship with the Christian Church. Lecturing, tutoring, evaluating and seminaring are practices that were formed in accordance with both monastic and clerical traditional forms of immuring knowledge. The world over, lecturers abide to the practice of offering sermons to an expectedly obedient public, turning non-Western class rooms into misguided and misunderstood versions of lay masses. The widespread use of syllabuses and bibliographies add to a conception of the class room as the place where canon is learned (even if to be later questioned, but not necessarily deconstructed). Critically analysing and questioning the roots and meanings of this class-room tradition seems to be a necessary propaedeutic step in the process of decolonizing the academy.